Case report: Durable response of immuno-chemotherapy targeting a rare ROS1 fusion-positive extensive-stage SCLC patient after primary resistance to crizotinib - Qiu, Mengli; Guo, Peiwen; Wang, Sisi; Zhu, Yong; Wu, Siqi; Peng, Huiting; Guo, Zehuai; Guo, Yanmeng; Lin, Jieheng; Cao, Yang (Frontiers in Pharmacology, 2025)
BackgroundSmall cell lung cancer (SCLC) is characterized by an exceedingly low mutation rate in oncogenic driver alterations, and there are currently no articles or case reports documenting SCLC patients carrying ROS1 fusions. Tyrosine kinase inhibitors (TKIs) have demonstrated significant efficacy and safety in patients with ROS1 fusion-positive non-small cell lung cancer (NSCLC). However, effective treatment modalities for ROS1 fusion-positive SCLC patients remain poorly defined.Materials and MethodsWe report the first case of an extensive-stage SCLC (ES-SCLC) patient harboring ROS1 fusion, along with TP53, RB1, PTEN, and TERT mutations. The patient exhibited primary resistance to a 3-week course of crizotinib as first-line treatment. Following this, the patient was administered second-line therapy, including chemotherapy coupled with immune checkpoint inhibitor (ICI) and ICI maintenance treatment, resulting in a partial response (PR). Notably, the clinical response to second-line therapy persisted for over 19 months, surpassing the previously reported efficacy of immuno-chemotherapy in ES-SCLC cases (5.7 months) while maintaining a satisfactory quality of life.ConclusionWe hypothesize that ROS1 fusion may not function as an oncogenic driver alteration in ES-SCLC. Immuno-chemotherapy, not ROS1-TKIs, might provide superior efficacy in ES-SCLC patients with ROS1 fusion.